The Influence of Personality and Work Discipline on the Performance of XXX Service Employees - Fauzi Farchan (Penerbit Hellow Pustaka, 2026)
All organizations strive to achieve their goals optimally. Organizational goals can be achieved through strong performance. However, several studies have shown that performance still falls short of expectations. Performance is influenced by several factors. However, this study focuses on personality and work discipline. This study aims to determine the influence of personality and work discipline on employee performance at Department XXX.To analyze the influence of personality and work discipline on employee performance at Department XXX, both individually and collectively, the method used is descriptive and associative or correlational research using a quantitative approach. The population in this study was the personality, work discipline, and performance of all 58 structural employees at Department XXX. The sample size for this study was 47 employees, with data collection using a questionnaire. Data analysis techniques used multiple regression analysis, correlation, coefficient of determination, and relative contributions between the independent and dependent variables, both individually and collectively. Calculations were performed using SPSS version 25 software.The results indicate that personality influences performance; Personality Variance can explain Performance Variance by 7.1%. There is an influence of Work Discipline on the Performance of XXX Service employees. Work Discipline Variance can explain Performance Variance by 11.8%; there is a joint influence of Personality and Work Discipline on Performance. Personality and Work Discipline Variance can explain Performance Variance by 24.3%. To improve performance, it is necessary to reconsider and improve personality and work discipline.